Measuring And Analyzing Changes In The Exchange Rate And Their Impact On The Trade Balance In Iraq 2010-2022 - Marwa Allawi Naji (Harmoni Economics: International Journal of Economics and Accounting, 2024)
This research seeks to illustrate the effects of rate of exchange volatility on Iraq's trade balance .The report examines currency rates in Iraq from 2010 to 2022, including both official and parallel values. The study addresses the trade balance, encompassing exports and imports, and investigates the impact of exchange rate fluctuations on trade performance through the ARDL model. It demonstrates a direct relationship between the two variables and confirms the absence of autocorrelation issues. Formulating a series of results and recommendations.